MAKNA DAN FUNGSI MANTRA MALAM SATU SURO DI DESA TULUNGREJO DUSUN JUNGGO KECAMATAN BUMIAJI KOTA BATU - Amanda, Aprillia Rizki; Wahyuni, M. Afri; Anggraini, Wulan Ria (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2018)
This study aims to identify the meaning and function of mantra malam satu suro in the hamlet Junggo, Tulungrejo village, Bumiaji district, Batu City. This research uses qualitative type. The method used in this research is descriptive method. The source of data used in this research is the text of mantra malam satu suro and informant. Data collection techniques conducted by interviewing and recording mantra spoken by informants. The results of this study are (1) the meaning of a mantra malam satu suro, containing the meaning of petition addressed to the spirits of the ancestors. (2) the function of a mantra malam satu suro, as a means of communicating the caretaker with the ancestral spirits of the village believed to help keep the people in the hamlet of Junggo.